2014
DOI: 10.1002/app.40900
|View full text |Cite
|
Sign up to set email alerts
|

Highly antibacterial and toughened polystyrene composites with silver nanoparticles modified tetrapod‐like zinc oxide whiskers

Abstract: In this work, high‐performance multifunctional composites were obtained by melt blending silver deposited tetrapod‐like zinc oxide whiskers (Ag‐ZnOw) with polystyrene (PS). The chemical, spectroscopic, antibacterial, mechanical, and morphological properties of the PS/Ag‐ZnOw composites were carefully investigated and discussed. The obtained PS/Ag‐ZnOw composites characterized remarkable antibacterial activity against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). Moreover, it is found that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Compared to PLA/NR/T‐ZnOw, the tensile and flexural strengths of PLA/NR/T‐ZnOw/GR were greatly improved with the loadings of 0.5 and 1 wt% GR (Figure 1c,d). This is due to the interactions formed between a small amount of GR and molecular chains in polymer, whose interfaces can effectively transfer stress when subjected to external load, showing the enhancement effect of inorganic particles 46 . However, as the GR loading beyond 1 wt%, the tensile properties of PLA/NR/T‐ZnOw/GR decreased depending on the increased GR loading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to PLA/NR/T‐ZnOw, the tensile and flexural strengths of PLA/NR/T‐ZnOw/GR were greatly improved with the loadings of 0.5 and 1 wt% GR (Figure 1c,d). This is due to the interactions formed between a small amount of GR and molecular chains in polymer, whose interfaces can effectively transfer stress when subjected to external load, showing the enhancement effect of inorganic particles 46 . However, as the GR loading beyond 1 wt%, the tensile properties of PLA/NR/T‐ZnOw/GR decreased depending on the increased GR loading.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the interactions formed between a small amount of GR and molecular chains in polymer, whose interfaces can effectively transfer stress when subjected to external load, showing the enhancement effect of inorganic particles. 46 However, as the GR loading beyond 1 wt%, the tensile properties of PLA/NR/T-ZnOw/GR decreased depending on the increased GR loading. The intercontacting in a lot of GR sheets results in the slip layers, whose slips in GR multilayers will decline the mechanical properties to a certain degree when the composite stressed.…”
Section: Mechanical Property Analysismentioning
confidence: 99%
“…This study selected three types of inorganic whiskers (needle-like calcium carbonate whisker (CaCOw), tetrapod-like zinc oxide whisker (T-ZnOw), needle-like, fusiform, or fan-shaped alkaline magnesium oxysulfate whisker (MOSw)), which are ecofriendly and do not form toxic compounds when reacting with other rubber components, and introduced them into the NRL matrix. Accordingly, we fabricated whiskers/NRL composites with excellent mechanical properties and antibacterial efficacy. These composites are highly durable and stop bacterial invasion at the source. We created a template, which has a rapid operation and strong universality, to observe the antibacterial effect of latex composites.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrolysis yield of precursor increased significantly with the increase of filler. Pan [9] et al Modified the surface of tetraacicular zinc oxide (T-ZnOw) by melt blending, deposited Ag on the surface of T-ZnOw, prepared Ag ZnOw, and added it into PS as filler to prepare high-performance multifunctional composites. It was found that the impact strength of the composites was also improved with the increase of Ag ZnO content.…”
Section: Introductionmentioning
confidence: 99%